Akidah dan Akhlak Pemuda Ashabul Kahfi: Tafsir al-Kasysyāf dalam Bingkai Sufistik al-Ghazālī - Sudarman, Susilo (Sunan Kalijaga Islamic State University, 2023)
The narrative of Ashabul Kahf, the seven young men who fled from an oppressive ruler, as portrayed in Surah al-Kahf, stands as a paradigmatic example of the Qur’an’s depiction of faith and moral integrity in young believers. Az-Zamakhsyari’s al-Kasysyaf offers an insightful interpretation of these verses, emphasizing elements that inspire the deepening of faith and the cultivation of moral excellence within the Muslim community through reflection on this story. This study, grounded in an ethical-Sufistic framework primarily informed by al-Ghazali, investigates the intersection of ethical concepts with az-Zamakhsyari’s exegetical approach. It explores two central questions: How does az-Zamakhsyari accentuate the depiction of faith and moral virtues in the account of Ashabul Kahf? And how can this portrayal be analyzed through the lens of ethical-Sufistic concepts? The research reveals that az-Zamakhsyari underscores, within his interpretive narrative, the courageous risk-taking of Ashabul Kahf in safeguarding their faith. They are depicted as individuals who mutually support each other, practice self-restraint, and engage in contemplative reasoning to attain wisdom. These qualities align closely with al-Ghazali’s ethical-Sufistic framework, which identifies praiseworthy virtues (al-akhlaq al-mahmudah) such as courage (al-syaja’ah), self-restraint (al-‘iffah), wisdom (al-hikmah), and balance (al-‘adl).